Determinants of Shareholder Gains in Acquisitions: An Empirical Study in the Indian Corporate Sector - Raghuvanshi, Abhishek; Raghuvanshi, Anvita (Indian Journal of Finance, 2014)
India today is witnessing a wave of mergers and acquisitions in this decade. This has important implications for not only the participating firms, but also for the shareholders investing in these firms. The firms thus need to understand the impact of acquisitions on the shareholders’ wealth in the Indian context. The present paper investigates the factors that have implications for shareholder gains on the announcement of acquisitions for both the target and acquiring firms. The empirical results obtained indicate that the target firms experience statistically significant higher gains than the acquiring firms around the announcement period window, as well as in the run up window. The gains for the target firms are more for target firms being paid higher premiums, while high premiums do not seem to have an adverse impact on the gains for the acquiring firms. Furthermore, the gains seem to be more for value acquirers than growth acquirers and are high in cases where the target firms are smaller as compared to the acquiring firms.